Mining and industrial processing wastes of phosphate rocks in Egypt: potentiality of rare earth elements - E. A. Abou El‑Anwar; M. A. Rashwan; M. A. Abd El Samee; Z. L. Belal; S. A. Salman; E. M. Seleem; W. Abdelwahab; Z. Abd El-Shakour; M. Kamal; A. S. Ahmed (International Journal of Environmental Science and Technology, 2025)
Globally, Egypt ranked the eighth position in the production of phosphorus with about 5 million tons annually. Phosphate ore is considered one of the commonest sources of rare earth elements (REEs). Mining and industrial processes (beneficiation) of phosphate ore produce huge amounts of wastes in different sizes. The present study aims to evaluate the potentiality of the phosphate ore wastes as a source of rare earth elements (REEs). The study targeted some phosphate production sites in Egypt, including: Abu Tartur, West and East El-Sebaiya phosphate mines, in addition to the fertilizers factory in Assiut. The collected waste samples, during 2023, were analyzed in terms of mineralogical composition using XRD (X-Ray Diffraction) and chemical composition using XRF (X-Ray Fluorescence). The results of chemical analysis recorded the highest concentrations of Y, Ce, La, Nd, Sc, Sm, U, and Th in Abu Tartur waste samples, while the lowest concentrations were recorded in the fertilizers factory waste samples. These wastes contain higher concentrations of REEs than the Algerian and USA wastes. Furthermore, an enrichment of the mostly environmental hazardous elements As, Cr, Cd, Pb, and Se are detected in Abu Tartur and West and East El-Sebaiya. Thus, the wastes from the industry and mining processing of phosphate represented a vital economic source for the production of REEs. The use of wastes for production of trace and rare earth elements represents an economic and environmental add value for phosphate industry.